ADVERSE DRUG REACTIONS (ADRS): FACTORS AND ROLE OF PHARMACIST IN THEIR PREVENTION - Bushra, Rabia; Baloch, Saba Ajaz; Jabeen, Aisha; Bano, Nusrat; Aslam, Nousheen (Journal of Ayub Medical College Abbottabad, 2015)
Adverse drug reactions (ADRs) are the undesirable effects of drugs even when administered in daily normal doses. It has been seen that ADRs may arise even after single administration of drug(s), however, long term therapies are more prone to ADRs. Currently it has become a burning issue all around the world and connected with financial expansion owing to hospitalization. Pharmacists are the custodians of drugs especially clinical pharmacists play a vital role in preventing the risks of ADRs. This review deals with the factors leading to possible ADRs, its prevention and the role of pharmacist in management of ADRs.